2020
DOI: 10.3390/jcm9103371
|View full text |Cite
|
Sign up to set email alerts
|

Stressful Life Events and the Clinical Expression of Obsessive–Compulsive Disorder (OCD): An Exploratory Study

Abstract: Background: In obsessive–compulsive disorder (OCD), symptom content and severity appear to fluctuate over the course of the life cycle in accordance with stressful life events. The objective of this paper was to compare OCD patients with and without reported stressful life events (SLEs) in terms of the sociodemographics of patients and the clinical characteristics of OCD. Methods: This was a cross-sectional study involving 1001 patients with OCD. Data concerning SLEs were collected via the Yale OCD Natural His… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 81 publications
(84 reference statements)
0
9
0
Order By: Relevance
“…There were significant correlations between obsessions about dirt, germs and viruses, and between those who engaged in compulsive hand washing and the likelihood that respondents had moderate/high stress. Increased general stress (for example, job loss and family disease) and changes in normal life routines are among the causes of severe obsessive–compulsive symptoms [ 50 ], and it is true about COVID-19 and the quarantine caused by it.…”
Section: Discussionmentioning
confidence: 99%
“…There were significant correlations between obsessions about dirt, germs and viruses, and between those who engaged in compulsive hand washing and the likelihood that respondents had moderate/high stress. Increased general stress (for example, job loss and family disease) and changes in normal life routines are among the causes of severe obsessive–compulsive symptoms [ 50 ], and it is true about COVID-19 and the quarantine caused by it.…”
Section: Discussionmentioning
confidence: 99%
“…This result may indicate that most dimensions of OCD have been negatively impacted by the pandemic, but some forms more significantly than others ( Wheaton et al, 2021 ). It is possible that any stressful life event could lead to a generalized increase in OCD severity ( Kracker Imthon et al, 2020 ). However, when assessing unique predictors, it was found that only higher scores on the contamination subscale were linked to COVID-19 concern and impairment by the pandemic, which is to be expected given the fears associated with this dimension.…”
Section: Discussionmentioning
confidence: 99%
“…In those with more marked alterations in these processes, a transition to clinical OCD occurs (Poletti et al, 2022b ). This may be more likely to happen at “critical” stages of the life cycle, or at any other period characterized by increased stress and a higher cognitive, affective or sensory load (Sousa-Lima et al, 2019 ; Imthon et al, 2020 ; Raposo-Lima and Morgado, 2020 ). Such periods include the transition from early to later childhood (Geller et al, 2001 ), the transition from adolescence to adulthood (Horwath and Weissman, 2000 ; Solmi et al, 2022 ), and pregnancy or childbirth in women (Starcevic et al, 2020 ).…”
Section: Integrating Bottom-up and Top-down Approaches In The Study O...mentioning
confidence: 99%